Solid electrolytic capacitors containing deoxidized anodes
The use of high CV/G ratio powder and controlled sintering process in solid electrolytic capacitors enhances electrical performance by minimizing leak current and maintaining stability under extreme conditions.
Patent Information
- Application Number
- JP2023512311
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-23
- Filing Date
- 2021-09-22
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2041-09-22
AI Technical Summary
Solid electrolytic capacitors using high CV/G ratio powders face issues with low sintered compression strength, leading to microcracks and inadequate electrical performance due to difficulty in impregnating small holes between particles, especially under extreme conditions.
A solid electrolytic capacitor design using a powder with a ratio of 35,000 μF·V/g or higher, combined with a controlled sintering process to form a porous anode body, dielectric, and solid electrolyte, achieving a normalized aged leak current of 0.1% or less.
The capacitor exhibits improved electrical performance with low leak current, stable capacitance, and high breakdown voltage under various conditions, including extreme temperatures and humidity levels.
Smart Images

Figure 0007626842000004 
Figure 0007626842000001 
Figure 0007626842000002
Abstract
Description
[Technical field]
[0001] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 082,071, having a filing date of September 23, 2020, which is incorporated by reference in its entirety. [Background technology]
[0002] Solid electrolytic capacitors (e.g., tantalum capacitors) are typically manufactured by pressing a metal powder (e.g., tantalum) around metal leads, sintering the pressed part, anodizing the sintered anode, and then applying a solid electrolyte. Unfortunately, one problem associated with many solid electrolytic capacitors is that when powders having a high specific charge ("CV / g") are used, the sintered anodes tend to have a relatively low degree of compressive strength. This can cause microcracks to form in the anode body, which can create potential failure sites in the capacitor under extreme conditions such as high temperature and / or high humidity levels. These problems are compounded in that high specific charge powders are generally formed from particles with very small dimensions and large surface areas, which results in the formation of small pores between the particles that are difficult to impregnate with the dielectric and solid electrolyte solutions. Difficulties in impregnating such small pores lead to the formation of a solid electrolyte that does not adhere well to the dielectric coating and is unlikely to achieve good surface coverage, which leads to poor electrical performance of the capacitor. Summary of the Invention [Problem to be solved by the invention]
[0003] Thus, there is currently a need for solid electrolytic capacitors with improved performance. [Means for solving the problem]
[0004] According to one embodiment of the present invention, a capacitor is disclosed that includes a capacitor element. The capacitor element includes a deoxidized and sintered anode body formed from a powder having a specific charge of about 35,000 μF·V / g or greater. Further, a dielectric is disposed on the anode body, and a solid electrolyte is disposed on the dielectric. The capacitor may also include a capacitor having a capacitance of the formula: Normalized aged leakage current = 100 x (aged DCL / CV) (In the formula, Aged DCL is the leakage current measured at approximately 23°C and rated voltage for approximately 60 seconds after a capacitor has been subjected to a life test at 85°C and rated voltage for 120 hours and then allowed to recover at approximately 23°C for 60 minutes; C is the desired initial capacitance (in Farads) at a temperature of approximately 23° C. and an operating frequency of 120 Hz; V is the rated voltage (volts) The resulting normalized aged leakage current is approximately 0.1% or less, as determined according to
[0005] According to another embodiment of the present invention, a method of forming a solid electrolytic capacitor is disclosed that includes forming an anode by a process that includes compressing a powder having a specific charge of about 35,000 μF·V / g or greater into a porous anode body, subjecting the porous anode body to a deoxidation process to form a deoxidized anode body, and sintering the deoxidized anode body, further anodizing the deoxidized and sintered anode body to form a dielectric disposed over the anode body, and forming a solid electrolyte disposed over the dielectric.
[0006] First, the claims of this application as filed will be described. [Claim 1] 1. A solid electrolytic capacitor including a capacitor element, the capacitor element including a deoxidized and sintered anode body formed from a powder having a specific charge of about 35,000 μF·V / g or greater, a dielectric disposed on the anode body, and a solid electrolyte disposed on the dielectric, the capacitor having a capacitance of about 1.0 μF·V / g or greater, the capacitance being determined by a formula: Normalized aged leakage current = 100 x (aged DCL / CV) (In the formula, Aged DCL is the leakage current measured at about 23° C. and rated voltage for about 60 seconds after the capacitor has been subjected to a life test at 85° C. and rated voltage for 120 hours and then allowed to recover at about 23° C. for 60 minutes; C is the desired initial capacitance (in Farads) at a temperature of approximately 23° C. and an operating frequency of 120 Hz; V is the rated voltage (volts) The solid electrolytic capacitor exhibits a normalized aged leakage current of about 0.1% or less, as determined according to [Claim 2] 10. The solid electrolytic capacitor of claim 1, wherein the aged DCL is about 0.5 μA or less. [Claim 3] 10. The solid electrolytic capacitor of claim 1, wherein the aged DCL is about 0.25 μA or less. [Claim 4] 10. The solid electrolytic capacitor of claim 1, wherein the normalized aged leakage current is less than or equal to about 0.0075%. [Claim 5] 10. The method of claim 1, wherein the anode body comprises tantalum and the dielectric comprises tantalum pentoxide. Solid electrolytic capacitor. [Claim 6] 10. The solid electrolytic capacitor of claim 1, wherein the solid comprises manganese dioxide. [Claim 7] an anode termination in electrical communication with the anode body; a cathode termination in electrical communication with the solid electrolyte; and a housing that encases the capacitor element and leaves at least a portion of the anode termination and the cathode termination exposed; The solid electrolytic capacitor of claim 1 further comprising: [Claim 8] 8. The solid electrolytic capacitor according to claim 7, wherein the housing is formed from a resin material that encapsulates the capacitor element. [Claim 9] 2. The solid electrolytic capacitor according to claim 1, wherein the powder has a specific charge of about 100,000 to about 300,000 μF·V / g. [Claim 10] 1. A method of forming a solid electrolytic capacitor, comprising: forming an anode by a process including compressing a powder having a specific charge of about 35,000 μF·V / g or greater into a porous anode body, subjecting the porous anode body to a deoxidization process to form a deoxidized anode body, and sintering the deoxidized anode body; anodizing the deoxidized and sintered anode body to form a dielectric disposed over the anode body; forming a solid electrolyte disposed over the dielectric; A method comprising: [Claim 11] The method of claim 10, wherein an anode lead is connected to the porous anode body. [Claim 12] The method of claim 10 , wherein the deoxidation process comprises inserting the porous anode body into a housing containing a getter material. [Claim 13] The method of claim 12, further comprising the step of heating the atmosphere of the enclosure to a temperature of about 700° C. to about 1,200° C. [Claim 14] 11. The method of claim 10, wherein the sintering step is carried out at a temperature of about 700°C to about 1,600°C. [Claim 15] The method of claim 10, further comprising the step of pre-sintering the porous anode body prior to the deoxidation process. [Claim 16] 11. The method of claim 10, wherein the powder comprises tantalum and the dielectric comprises tantalum pentoxide. [Claim 17] The capacitor has the following formula: Normalized aged leakage current = 100 x (aged DCL / CV) (In the formula, Aged DCL is the leakage current measured at about 23° C. and rated voltage for about 60 seconds after the capacitor has been subjected to a life test at 85° C. and rated voltage for 120 hours and then allowed to recover at about 23° C. for 60 minutes; C is the desired initial capacitance (in Farads) at a temperature of approximately 23° C. and an operating frequency of 120 Hz; V is the rated voltage (volts) 11. The method of claim 10, wherein the normalized aged leakage current, as determined according to: [Claim 18] 18. The method of claim 17, wherein the aged DCL is about 0.5 μA or less. [Claim 19] 18. The method of claim 17, wherein the aged DCL is about 0.25 μA or less. [Claim 20] 20. The method of claim 17, wherein the normalized aged leakage current is less than or equal to about 0.0075%. [Claim 21] 11. The method of claim 10, wherein the powder has a specific charge of about 100,000 to about 300,000 μF·V / g. [Claim 22] The method of claim 10 , wherein the solid electrolyte comprises manganese dioxide. Other features and aspects of the invention are set forth in greater detail below.
[0007] A full and enabling disclosure of the present invention, including the best mode thereof, directed to one of ordinary skill in the art, is set forth more particularly in the remainder of the specification, which makes reference to the appended drawings, in which: [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a cross-sectional view of one embodiment of a capacitor of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] It will be appreciated by those skilled in the art that this discussion is a description of exemplary embodiments only and is not intended to limit the broader aspects of the invention, which may be embodied in the exemplary configurations.
[0010] Generally speaking, the present invention is directed to a capacitor capable of exhibiting good electrical properties under a wide range of different conditions. More specifically, the capacitor includes a capacitor element including a sintered porous anode body and a dielectric disposed on the anode body. The anode body is formed from a powder including a valve metal (i.e., a metal that can be oxidized) or a valve metal-based compound, such as tantalum, niobium, aluminum, hafnium, titanium, alloys thereof, oxides thereof, nitrides thereof, and the like. The powder has a relatively high specific charge, such as about 35,000 μF·V / g or more, in some embodiments about 50,000 μF·V / g or more, in some embodiments about 70,000 to about 350,000 μF·V / g, in some embodiments about 80,000 to about 325,000 μF·V / g, and in some embodiments about 100,000 to about 300,000 μF·V / g. As is known in the art, the specific charge can be determined by multiplying the capacitance by the anodization voltage used and then dividing this product by the weight of the anodized electrode body.
[0011] During formation of the capacitor, the anode body is compressed and then deoxidized to minimize the presence of oxygen within the anode body. The resulting anode body may therefore have a relatively low oxygen content. For example, the anode body may have about 5,500 ppm or less of oxygen, in some embodiments about 5,000 ppm or less of oxygen, and in some embodiments about 500 to about 4,500 ppm of oxygen. The oxygen content may be measured by a LECO Oxygen Analyzer and includes oxygen in the native oxide film on the tantalum surface and bulk oxygen in the tantalum particles. The bulk oxygen content is controlled by the periodicity of the tantalum crystal lattice, which increases linearly with increasing oxygen content in the tantalum until the solubility limit is reached. This method is described in "Critical Oxygen Content In Porous Anodes Of Solid Tantalum Capacitors", Pozdeev-Freeman et al., Journal of Materials Science: Materials In Electronics 9, (1998) 309-311, where X-ray diffraction analysis (XRDA) was used to measure the periodicity of the tantalum crystal lattice. Oxygen in sintered tantalum anodes can be confined to a thin native surface oxide film, while the bulk of the tantalum is virtually oxygen-free.
[0012] The present inventors have discovered that by selective control over certain aspects of the deoxidation process, the resulting capacitor can have many unique and beneficial properties. For example, a sintered anode body can be produced in a mass fraction of about one kilogram ("kg") f ") or more, in some embodiments, about 5 kg f In some embodiments, the amount is about 10 to about 100 kg. f The anode bodies may exhibit high compressive strengths, such as 0.1 to 1.0 MPa. Among other things, high compressive strength can help limit the formation of microcracks in the anode body, which results in better capacitor electrical performance over a wide range of extreme conditions, such as high temperature and / or humidity levels. Minimizing oxygen content using certain deoxidation processes described herein can also enhance the degree of permeation of the dielectric and solid electrolyte, thereby further improving electrical performance.
[0013] The capacitors may, for example, exhibit low leakage currents ("DCL") under a variety of conditions. More specifically, the capacitors may exhibit a DCL of only about 20 microamps ("μA") or less, in some embodiments about 10 μA or less, in some embodiments about 5 μA or less, in some embodiments about 1 μA or less, in some embodiments about 0.5 μA or less, and in some embodiments about 0.01 to about 0.3 μA at a temperature of about 23° C. after being subjected to an applied voltage (e.g., rated voltage, or a multiple of the rated voltage, such as 1.1×rated voltage) for a period of about 5 seconds to about 500 seconds, and in some embodiments 20 seconds to about 400 seconds (e.g., 60 seconds or 300 seconds). Of course, the absolute value of the DCL may depend on the particular aspects of the capacitor, including the specific charge of the powder, the dimensions of the capacitor elements, and the like. In this regard, the normalized DCL may be calculated according to the following formula: Normalized DCL=100×(DCL / CV) where C is the initial capacitance in Farads and V is the rated voltage in Volts. It can be calculated as a percentage of the nominal charge by:
[0014] For example, capacitors of the present invention may exhibit a normalized DCL of about 0.5% or less, in some embodiments about 0.2% or less, in some embodiments about 0.1% or less, in some embodiments about 0.09% or less, in some embodiments about 0.08% or less, and in some embodiments about 0.01% to about 0.07%, measured at a temperature of about 23° C. after being subjected to an applied voltage (e.g., the rated voltage, or a multiple of the rated voltage, such as 1.1 x the rated voltage) for a period of about 5 seconds to about 500 seconds, and in some embodiments, 20 seconds to about 400 seconds (e.g., 60 seconds or 300 seconds).
[0015] In particular, the low DCL values may remain stable even at high temperatures. For example, the capacitors may exhibit "aged" DCL values within the above ranges even after being subjected to life testing at temperatures of about 80° C. or greater, and in some embodiments, from about 85° C. to about 150° C. (e.g., about 85° C., 105° C., 125° C., or 150° C.), for a substantial period of time, such as about 50 hours or greater, and in some embodiments, from about 100 hours to about 3,000 hours, and in some embodiments, from about 120 hours to about 2,500 hours (e.g., 120, 250, 500, 750, or 1,000 hours). In one embodiment, for example, the aged DCL of a capacitor after 120 hours of life testing at high temperature (e.g., about 85° C.) and 60 minutes of recovery at room temperature (e.g., about 23° C.) can be about 0.5 μA or less, in some embodiments about 0.3 μA or less, in some embodiments about 0.25 μA or less, in some embodiments about 0.2 μA or less, and in some embodiments about 0.01 to about 0.1 μA. Furthermore, the ratio of the aged DCL of a capacitor after 120 hours of exposure to high temperature (e.g., about 85° C.) and 60 minutes of recovery at room temperature (e.g., about 23° C.) to the initial DCL of the capacitor (e.g., at about 23° C.) can be about 5 or less, in some embodiments about 3 or less, in some embodiments about 2 or less, in some embodiments about 1.5 or less, and in some embodiments about 0.6 to about 1.2. Furthermore, the normalized aged DCL of a capacitor can be calculated according to the following formula: Normalized aged DCL = 100 × (aged DCL / CV) (Where, aged DCL is the leakage current after 120 hours of life testing at 85°C and 60 minutes of recovery at room temperature (approximately 23°C), C is the initial capacitance in Farads, and V is the rated voltage in Volts.) It can be calculated as a percentage of the nominal charge by:
[0016] The normalized aged DCL can be about 0.1% or less, in some embodiments about 0.075% or less, in some embodiments about 0.07% or less, in some embodiments about 0.065% or less, in some embodiments about 0.06% or less, and in some embodiments about 0.001 to about 0.006%. Additionally, the ratio of the normalized aged DCL of the capacitor after 120 hours exposure to elevated temperature (e.g., about 85° C.) and 60 minutes recovery to the initial normalized aged DCL of the capacitor (e.g., at about 23° C.) can also be about 5 or less, in some embodiments about 3 or less, in some embodiments about 2 or less, in some embodiments about 1.5 or less, and in some embodiments about 0.6 to about 1.2.
[0017] Other electrical properties of the capacitor may also remain good and stable under a variety of conditions. For example, the capacitor may also exhibit a relatively low equivalent series resistance (ESR), such as about 200 milliohms, in some embodiments less than about 150 milliohms, in some embodiments from about 0.01 to about 125 milliohms, and in some embodiments from about 0.1 to about 100 milliohms, measured at an operating frequency of 100 kHz and a temperature of 23° C. The capacitor may also exhibit such ESR values after exposure to temperatures of about 80° C. or higher, in some embodiments from about 100° C. to about 150° C., and in some embodiments from about 105° C. to about 130° C. (e.g., 105° C. or 125° C.), for a significant period of time, such as about 100 hours or more, in some embodiments from about 150 hours to about 3,000 hours (e.g., 3,000 hours). In one embodiment, for example, the ratio of the ESR of the capacitor after 3,000 hours of exposure to high temperature (e.g., 105°C) to the initial ESR value of the capacitor (e.g., at 23°C) is about 2.0 or less, in some embodiments about 1.5 or less, and in some embodiments, about 1.0 to about 1.3. Furthermore, the ratio of the capacitance after repeated cycles of the surge voltage ("charge and discharge capacitance") to the initial capacitance value before such testing can be about 0.7 to 1, in some embodiments about 0.8 to 1, in some embodiments about 0.9 to 1, and in some embodiments 0.91 to 0.99. The surge voltage can be applied for 4,000 to 16,000 cycles (e.g., 4,000, 8,000, 12,000, or 16,000 cycles). Moreover, the capacitance may also remain stable after exposure to elevated temperatures, such as about 80° C. or greater, in some embodiments from about 100° C. to about 150° C., in some embodiments from about 105° C. to about 130° C. (e.g., 105° C. or 125° C.), for a significant period of time, such as about 100 hours or greater, in some embodiments from about 150 hours to about 3,000 hours (e.g., 3,000 hours).In one embodiment, for example, the ratio of capacitance after 3,000 hours of exposure to high temperature (e.g., 105° C.) to the initial capacitance value (e.g., at 23° C.) is about 0.7 to 1, in some embodiments about 0.8 to 1, in some embodiments about 0.9 to 1, and in some embodiments about 0.91 to 0.99. Actual capacitance values (dry) may vary, but are typically about 1 millifarad per square centimeter ("mF / cm"), measured at a frequency of 120 Hz. 2 ") or more, in some embodiments, about 2 mF / cm 2 In some embodiments, the range is about 5 to about 50 mF / cm 2 In some embodiments, from about 8 to about 20 mF / cm 2 It is.
[0018] The capacitors can also exhibit a high percentage of their wet capacitance, allowing them to have only a small capacitance loss and / or variation in the presence of atmospheric humidity. This performance characteristic is determined by the formula: Wet to dry capacitance = (dry capacitance / wet capacitance) x 100 The capacitance is quantified by the "wet to dry capacitance percent" given by:
[0019] The present capacitors may exhibit a wet to dry capacitance percent of about 50% or greater, in some embodiments about 60% or greater, in some embodiments about 70% or greater, and in some embodiments, about 80%-100%.
[0020] It is also believed that the dissipation factor of the capacitor can be maintained at a relatively low level. Dissipation factor generally refers to the losses that occur in a capacitor and is usually expressed as a percentage of ideal capacitor performance. For example, the dissipation factor of the capacitor is typically about 250% or less, in some embodiments about 200% or less, and in some embodiments about 1% to about 180% at a frequency of 120 Hz. The capacitor can also be used in high voltage applications, such as rated voltages of about 35 volts or more, in some embodiments about 50 volts or more, and in some embodiments about 60 volts to about 200 volts. The capacitor can exhibit a relatively high "breakdown voltage" (the voltage at which the capacitor breaks down), such as, for example, about 60 volts or more, in some embodiments about 70 volts or more, in some embodiments about 80 volts or more, and in some embodiments about 100 volts to about 300 volts. Furthermore, the capacitor can also withstand relatively high surge currents that are also common in high voltage applications. The peak surge current may be, for example, greater than or equal to about 100 amps, in some embodiments greater than or equal to about 200 amps, and in some embodiments, between about 300 amps and about 800 amps.
[0021] Various embodiments of the invention will now be described in more detail.
[0022] I. Capacitor Element A. Anode body As described above, the anode body is formed from a powder including a valve metal or a valve metal-based compound. In one embodiment, for example, the powder is formed from tantalum. If desired, a reduction process may be used in which a tantalum salt (e.g., potassium fluorotantalate (K2TaF7), sodium fluorotantalate (Na2TaF7), tantalum pentachloride (TaCl5), etc.) is reacted with a reducing agent. The reducing agent can be provided in the form of a liquid, a gas (e.g., hydrogen), or a solid, such as a metal (e.g., sodium), a metal alloy, or a metal salt. For example, in one embodiment, a tantalum salt (e.g., TaCl5) can be heated at a temperature of about 900°C to about 2,000°C, in some embodiments about 1,000°C to about 1,800°C, and in some embodiments about 1,100°C to about 1,600°C to form a vapor, which can be reduced in the presence of a gaseous reducing agent (e.g., hydrogen). Further details of such reduction reactions are described in WO-2014 / 199480 by Maeshima et al. After reduction, the product can be cooled, crushed, and washed to form a powder.
[0023] The powder may be a free-flowing fine powder comprising primary particles. The primary particles of the powder generally have a median diameter (D50) of about 5 to about 250 nanometers, in some embodiments about 10 to about 200 nanometers, and in some embodiments about 20 to about 150 nanometers, as determined, for example, using a laser particle size distribution analyzer (e.g., LS-230) from BECKMAN COULTER Corporation, optionally after subjecting the particles to ultrasonic vibration for 70 seconds. Primary particles typically have a three-dimensional particle shape (e.g., spherical or angular). Such particles typically have a relatively low "aspect ratio," i.e., the average diameter or width of the particle divided by the average thickness (D / T). For example, the aspect ratio of the particles may be about 4 or less, in some embodiments about 3 or less, and in some embodiments about 1 to about 2. In addition to primary particles, the powder may include other types of particles, such as secondary particles formed by aggregation (or agglomeration) of the primary particles. Such secondary particles may have a median diameter (D50) of from about 1 to about 500 micrometers, and in some embodiments, from about 10 to about 250 micrometers.
[0024] The particles can be aggregated by heating the particles and / or by using a binder, for example, at a temperature of from about 0° C. to about 40° C., in some embodiments from about 5° C. to about 35° C., and in some embodiments from about 15° C. to about 30° C. Suitable binders also include, for example, poly(vinyl butyral); poly(vinyl acetate); poly(vinyl alcohol); poly(vinylpyrrolidone); cellulose polymers such as carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and methylhydroxyethyl cellulose; atactic polypropylene, polyethylene; polyethylene glycols (e.g., Carbowax from Dow Chemical Co.); polystyrene, poly(butadiene / styrene); polyamides, polyimides, and polyacrylamides, high molecular weight polyethers; copolymers of ethylene oxide and propylene oxide; fluoropolymers such as polytetrafluoroethylene, polyvinylidene fluoride, and fluoroolefin copolymers; acrylic polymers such as sodium polyacrylate, poly(lower alkyl acrylates), poly(lower alkyl methacrylates), and copolymers of lower alkyl acrylates and methacrylates; and fatty acids and waxes such as stearic acid and other soap fatty acids, vegetable waxes, microcrystalline waxes (refined paraffins), and the like. If desired, the powders can be doped with a sintering inhibitor in the presence of a dopant such as an aqueous acid (e.g., phosphoric acid). The amount of dopant added depends in part on the surface area of the powder, but is typically present in an amount of about 200 ppm (parts per million) or less. The dopant may be added before, during, and / or after agglomeration. The powder may also be subjected to one or more deoxidation treatments. For example, the powder may be exposed to a getter material (e.g., magnesium) as described in U.S. Pat. No. 4,960,471. The temperature at which the powder is deoxidized may vary, but typically ranges from about 700° C. to about 1,600° C., in some embodiments from about 750° C. to about 1,200° C., and in some embodiments from about 800° C. to about 1,000° C. The total time for the deoxidation treatment may range from about 20 minutes to about 3 hours.
[0025] The resulting powder has certain properties that enhance its ability to function as a capacitor anode. For example, the powder typically has a particle size of about 0.5 to about 10.0 μm. 2 / g, in some embodiments from about 0.7 to about 5.0 m 2 / g, in some embodiments from about 2.0 to about 4.0 m 2 / g. Furthermore, the bulk density of the powder is about 0.1 to about 0.8 grams per cubic centimeter (g / cm 3 ), and in some embodiments, from about 0.2 to about 0.6 g / cm 3 and in some embodiments, from about 0.4 to about 0.6 g / cm 3 It could be.
[0026] Once the powder is formed, it is then typically compressed or pressed to form pellets using any conventional powder pressing equipment. For example, a press can be used that is a single station compression press that includes a die and one or more punches. Alternatively, an anvil type compression press can be used that uses only a die and a single lower punch. Single station compression presses are available in several basic types such as cam presses, toggle / knuckle presses, and eccentric / crank presses with various capabilities such as single action, double action, floating die, moving platen, opposed ram, screw, impact, hot pressing, coining, or sizing. Powders are typically compressed or pressed at a rate of about 0.5 to about 20 g / cm. 3 In some embodiments, from about 1 to about 15 g / cm 3 In some embodiments, from about 2 to about 10 g / cm 3The powder is pressed to a density of 10 ...
[0027] After removal of the binder, the anode body may be subjected to a deoxidation process. In one embodiment, for example, the deoxidation process involves exposing the anode body to a getter material (e.g., magnesium, titanium, etc.) capable of removing oxygen from the anode body by chemical reaction, adsorption, etc. More specifically, the anode body is first inserted into a housing (e.g., a tantalum box) that also contains the getter material. The atmosphere within the housing is typically an inert atmosphere (e.g., argon gas). To initiate deoxidation, the atmosphere within the housing is heated to a temperature sufficient to melt and / or vaporize the getter material and deoxidize the anode body. The temperature may vary depending on the charge to charge ratio of the anode powder, but typically ranges from about 700°C to about 1,200°C, in some embodiments from about 750°C to about 1,100°C, and in some embodiments from about 800°C to about 1,000°C. The total time for deoxidation may range from about 20 minutes to about 3 hours. This may be done in one or more steps. Once deoxidation is complete, the getter material typically vaporizes and forms a deposit on the walls of the housing. To ensure removal of the getter material, the anode body may also be subjected to one or more acid leaching steps, such as with solutions of nitric acid, hydrofluoric acid, hydrogen peroxide, sulfuric acid, water, or the like, or combinations thereof.
[0028] After deoxidation, the anode body can be sintered to form a porous monolithic mass. The anode body is typically sintered at a temperature of about 700°C to about 1,600°C, in some embodiments about 800°C to about 1,500°C, in some embodiments about 900°C to about 1,200°C, for about 5 minutes to about 100 minutes, in some embodiments about 8 minutes to about 15 minutes. This can be done in one or more steps. If desired, the sintering can be done in an atmosphere that limits the movement of oxygen atoms to the anode body. For example, the sintering can be done in a reducing or inert atmosphere, such as in a vacuum, in an inert gas, or in hydrogen. The reducing atmosphere can be at a pressure of about 10 Torr to about 2000 Torr, in some embodiments about 100 Torr to about 1000 Torr, and in some embodiments about 100 Torr to about 930 Torr. Mixtures of hydrogen and other gases (e.g., argon or nitrogen) can also be used. As described above, sintering of the anode body is generally done after deoxidation. However, it should be understood that the anode body may be subjected to one or more pre-sintering steps prior to oxidation to aid in achieving the desired degree of green strength in the deoxidation process. Such pre-sintering steps may be performed under the same or different conditions as the sintering process performed after deoxidation. For example, pre-sintering may be performed in one or more steps at temperatures of about 700° C. to about 1,600° C., in some embodiments about 800° C. to about 1,500° C., in some embodiments about 900° C. to about 1,200° C., for about 5 minutes to about 100 minutes, in some embodiments about 8 minutes to about 15 minutes. Pre-sintering may also be performed in a reducing atmosphere, such as in vacuum, in an inert gas, or in hydrogen, as described above.
[0029] B. Dielectric The anode body is coated with a dielectric. The dielectric can be formed by anodizing the sintered anode body such that a dielectric layer is formed on and / or within the anode body. For example, a tantalum (Ta) anode can be anodized to tantalum pentoxide (Ta2O5). Typically, anodization is performed by first applying a solution to the anode, such as by immersing the anode in the electrolyte. A solvent such as water (e.g., deionized water) is commonly used. To enhance ionic conductivity, compounds that can dissociate in the solvent to form ions can be used. Examples of such compounds include acids, such as those described below with respect to the electrolyte. For example, an acid (e.g., phosphoric acid) can comprise about 0.01% to about 5% by weight, in some embodiments about 0.05% to about 0.8% by weight, and in some embodiments about 0.1% to about 0.5% by weight of the anodization solution. Blends of acids can also be used if desired.
[0030] A current can be passed through the anodizing solution to form the dielectric layer. The thickness of the dielectric layer is controlled by the value of the formation voltage. For example, the power supply can first be set in constant current mode until the required voltage is reached. The power supply can then be switched to potentiostatic mode to ensure that the desired dielectric thickness is formed over the entire surface of the anode. Of course, other known methods such as pulse or step potentiostatic methods can also be used. The formation voltage used during anodization is generally about 20 volts or more, in some embodiments about 30 volts or more, in some embodiments about 35 volts or more, and in some embodiments about 35 to about 70 volts, at a temperature in the range of about 10° C. or more, in some embodiments about 20° C. to about 200° C., and in some embodiments about 30° C. to about 100° C. The resulting dielectric layer can be formed on the surface of the anode and in its pores.
[0031] By selectively controlling the particular manner in which the anode body is formed, the inventors have found that the resulting capacitor can exhibit a high degree of dielectric strength that can improve capacitance stability. "Dielectric strength" generally refers to the ratio of the "breakdown voltage" of a capacitor (the voltage at which the capacitor breaks down, in volts, "V") to the thickness of the dielectric (in nanometers, "nm"). The present capacitors typically exhibit a dielectric strength of about 0.4 V / nm or greater, in some embodiments about 0.45 V / nm or greater, in some embodiments about 0.5 V / nm or greater, in some embodiments about 0.55 to about 1 V / nm, and in some embodiments about 0.6 to about 0.9 V / nm. The capacitor may exhibit a relatively high breakdown voltage, such as about 30 volts or more, in some embodiments about 35 volts or more, in some embodiments about 50 volts or more, in some embodiments about 65 volts or more, in some embodiments about 85 volts or more, in some embodiments about 90 volts or more, in some embodiments about 95 volts or more, in some embodiments about 100 volts to about 300 volts, as determined, for example, by increasing the applied voltage in 3 volt increments until the leakage current reaches 1 mA. Although the thickness may generally vary depending on the particular location of the anode body, the "dielectric thickness" for purposes of determining dielectric strength is generally considered to be the maximum thickness of the dielectric, which is typically in the range of about 50 to about 500 nm, in some embodiments about 80 to about 350 nm, and in some embodiments about 100 to about 300 nm. The dielectric thickness may be measured using a Zeiss Sigma FESEM at magnifications of 20,000x to 50,000x, where the sample is prepared by cutting the finished part in a plane perpendicular to the longest dimension of the finished part, and the thickness is measured where the cut is made perpendicularly through the dielectric layer.
[0032] C. solid electrolyte The solid electrolyte is disposed on the dielectric. Typically, the total thickness of the solid electrolyte is about 1 to about 50 μm, and in some embodiments, about 5 to about 20 μm. The solid electrolyte can include one or more layers of a conductive inorganic oxide (e.g., manganese dioxide), a conductive polymer (e.g., polyheterocycles such as polypyrroles, polythiophenes, polyanilines, polyacetylenes, poly-p-phenylenes, polyphenolates, and the like), and the like. In one embodiment, for example, the solid electrolyte can include manganese dioxide. As known in the art, manganese dioxide can be formed by pyrolysis of manganese nitrate (Mn(NO3)2), as described in U.S. Pat. No. 4,945,452 to Sturmer et al. Heating can be performed, for example, in a furnace at a temperature of about 150° C. to about 300° C., in some embodiments, about 180° C. to about 290° C., and in some embodiments, about 190° C. to about 260° C. Heating can be performed in a wet or dry atmosphere. The time for conversion depends on the furnace temperature, heat transfer rate, and atmosphere, but is generally about 3 to about 5 minutes. After pyrolysis, leakage current may sometimes increase due to damage sustained by the dielectric film during manganese dioxide deposition. To help further reduce this leakage, the capacitor may be reformed in an anodizing bath as known in the art. For example, the capacitor may be immersed in an electrolyte such as those described above and then subjected to a DC current.
[0033] D. Moisture Barrier Layer If desired, a moisture barrier layer disposed over the solid electrolyte may be used. The moisture barrier layer may be formed from a variety of different materials, such as hydrophobic elastomers, e.g., silicones, fluoropolymers, and the like. Silicone polymers are particularly suitable for use in the moisture barrier layer of the present invention. Such elastomers typically have the general formula:
[0034] [ka] (In the formula, x is an integer greater than 1; R1, R2, R3, R4, R5, R6, R7, and R8 are independently monovalent groups typically containing from 1 to about 20 carbon atoms, such as alkyl groups (e.g., methyl, ethyl, propyl, pentyl, octyl, undecyl, octadecyl, etc.); alkoxy groups (e.g., methoxy, ethoxy, propoxy, etc.); carboxyalkyl groups (e.g., acetyl); cycloalkyl groups (e.g., cyclohexyl); alkenyl groups (e.g., vinyl, allyl, butenyl, hexenyl, etc.); aryl groups (e.g., phenyl, tolyl, xylyl, benzyl, 2-phenylethyl, etc.); and halogenated hydrocarbon groups (e.g., 3,3,3-trifluoropropyl, 3-chloropropyl, dichlorophenyl, etc.). The polyorganosiloxanes are derived from polyorganosiloxanes such as those having the formula: ##STR00001## Examples of such polyorganosiloxanes include, for example, polydimethylsiloxanes ("PDMS"), polymethylhydrogensiloxanes, dimethyldiphenylpolysiloxanes, dimethyl / methylphenylpolysiloxanes, polymethylphenylsiloxanes, methylphenyl / dimethylsiloxanes, vinyldimethyl terminated polydimethylsiloxanes, vinylmethyl / dimethylpolysiloxanes, vinyldimethyl terminated vinylmethyl / dimethylpolysiloxanes, divinylmethyl terminated polydimethylsiloxanes, vinylphenylmethyl terminated polydimethylsiloxanes, dimethylhydro terminated polydimethylsiloxanes, methylhydro / dimethylpolysiloxanes, methylhydro terminated methyloctylpolysiloxanes, methylhydro / phenylmethylpolysiloxanes, fluorine modified polysiloxanes, and the like. To form elastomers, the polyorganosiloxanes can be crosslinked using any of a variety of known techniques, such as by catalytic cure (e.g., platinum catalysis), room temperature vulcanization, moisture cure, and the like. Crosslinkers such as alkoxysilanes having the formula Si-OR, where R is H, alkyl (eg, methyl), alkenyl, carboxylalkyl (eg, acetyl), etc., can be used.
[0035] In addition to being hydrophobic, it is generally desirable for the material used to form the moisture barrier layer to have a relatively low modulus of elasticity and a degree of flexibility, which may help absorb some of the thermal stresses caused by the expansion of the casing and allow it to undergo compressive forces. The flexibility of the material may be characterized by a correspondingly low modulus of elasticity ("Young's modulus"), such as about 5,000 kilopascals ("kPa") or less, in some embodiments about 1 to about 2,000 kPa, and in some embodiments about 2 to about 500 kPa, measured at a temperature of about 25°C. The material also typically has a degree of strength that allows it to retain its shape even when subjected to compressive forces. For example, the material may have a tensile strength of about 1 to about 5,000 kPa, in some embodiments about 10 to about 2,000 kPa, and in some embodiments about 50 to about 1,000 kPa, measured at a temperature of about 25°C. The above conditions allow the hydrophobic elastomer to further enhance the ability of the capacitor to function under extreme conditions.
[0036] Non-conductive fillers may be used in the moisture barrier layer to help achieve the desired flexibility and strength properties. If used, such additives typically comprise from about 0.5% to about 30% by weight, in some embodiments from about 1% to about 25% by weight, and in some embodiments from about 2% to about 20% by weight of the moisture barrier layer. Silicone elastomers may comprise from about 70% to about 99.5% by weight, in some embodiments from about 75% to about 99% by weight, and in some embodiments from about 80% to about 98% by weight of the moisture barrier layer. One particular example of such a filler includes, for example, silica. While most forms of silica contain a relatively hydrophilic surface due to the presence of silanol groups (Si-OH), silica has a surface that is (CH3) nThe surface may optionally be treated to include -Si- groups, where n is an integer from 1 to 3, which further enhances the hydrophobicity of the moisture barrier layer. The surface treatment agent may be, for example, an organosilicon compound monomer having a hydrolyzable group or a partial hydrolyzate thereof. Examples of such compounds include organosilazanes, silane coupling agents as described above, and the like.
[0037] The moisture barrier layer may be applied to any surface of the capacitor to achieve desired properties. For example, the moisture barrier layer may be disposed on the top, bottom, and / or side surfaces of the capacitor. The moisture barrier layer may also be disposed on the front and / or back surfaces of the capacitor. The moisture barrier layer may cover the entire area of the surface to which it is applied, or only a portion of the area. In one embodiment, for example, the moisture barrier layer covers about 30% or more, in some embodiments about 40% or more, and in some embodiments about 50% or more of the surface of the capacitor to which it is applied.
[0038] For example, referring to FIG. 1, one embodiment of a capacitor 30 is shown including a capacitor element 33 having a generally rectangular shape and including a front surface 36, a rear surface 38, a top surface 37, a bottom surface 39, a first side 32, and a second side (not shown). In the embodiment shown, an anode lead 16 is embedded within an anode body 40 and extends longitudinally from the front surface 36 of the capacitor element 33. Alternatively, the anode lead 16 may simply be connected (e.g., welded) to the front surface 36 of the capacitor element 33. The capacitor element 33 includes a dielectric (not shown) disposed over the anode body 40, a solid electrolyte 44 disposed over the dielectric, and a cathode coating 46 disposed over the solid electrolyte 44. As shown, the solid electrolyte 44 and the cathode coating 46 are typically present on each surface of the capacitor 30 except for the front surface 36. Of course, it should be understood that such layers may be applied to any surface of the capacitor and need not be applied in the manner shown.
[0039] The capacitor element 33 also includes an optional moisture barrier layer 63 comprising a hydrophobic material. In this particular embodiment, the moisture barrier layer 63 is disposed over the solid electrolyte 44 on the rear surface 38, the top surface 37, as well as the sides (not shown). The moisture barrier layer 63 is also present on the front surface 36, but need not necessarily be disposed over the solid electrolyte on this surface as described above. Of course, it should be understood that the moisture barrier layer 63 need not be disposed on the surface of the capacitor element 33 as shown in FIG. 1. In another embodiment, for example, the moisture barrier layer may be disposed only on the sides of the capacitor element 33. Regardless of where it is disposed, the moisture barrier layer can cover any desired portion of the surface. For example, the moisture barrier layer can cover substantially all of the surface on which they are disposed, such as about 90% or more, and in some embodiments, about 95% or more. But again, this is merely optional and the layer need not cover such a substantial portion of the surface.
[0040] E. Other optional components Other layers known in the art may also be included in the capacitor element, if desired. For example, an adhesive layer may optionally be formed between the dielectric and the solid electrolyte. The adhesive layer is typically formed from a relatively insulating resinous material (natural or synthetic). Such materials have a resistivity of greater than about 10 Ω·cm, in some embodiments greater than about 100, in some embodiments greater than about 1,000 Ω·cm, and in some embodiments, about 1×10 5 Ω cm, in some embodiments, greater than about 1×10 10It may have a resistivity of more than Ω·cm. Some resinous materials that may be utilized in the present invention include, but are not limited to, polyurethane, polystyrene, esters of unsaturated or saturated fatty acids (e.g., glycerides), and the like. For example, suitable esters of fatty acids include, but are not limited to, esters of lauric acid, myristic acid, palmitic acid, stearic acid, eleostearic acid, oleic acid, linoleic acid, linolenic acid, arolic acid, shellolic acid, and the like. These esters of fatty acids have been found to be particularly useful when used in relatively complex combinations to form "drying oils," which allow the resulting film to rapidly polymerize into a stable layer. Such drying oils may include mono-, di-, and / or tri-glycerides having a glycerol backbone with one, two, and three fatty acyl residues, respectively, that are esterified. For example, some suitable drying oils that may be used include, but are not limited to, olive oil, linseed oil, castor oil, tung oil, soybean oil, and shellac. These and other adhesive layer materials are described in more detail in US Pat. No. 6,674,635 to Fife et al.
[0041] If desired, the component may also be provided with a carbon layer (e.g., graphite) and a silver layer, respectively. The silver coating may act, for example, as a solderable conductor, contact layer, and / or current collector in a capacitor, and the carbon coating may limit the silver coating from contacting the solid electrolyte. Such coatings may cover part or all of the solid electrolyte.
[0042] II. termination Once formed, the capacitor element may be provided with terminations, particularly for use in surface mount applications. For example, the capacitor may include an anode termination to which the anode lead of the capacitor element is electrically connected, and a cathode termination to which the cathode of the capacitor element is electrically connected. Any conductive material may be used to form the terminations, such as conductive metals (e.g., copper, nickel, silver, nickel, zinc, tin, palladium, lead, copper, aluminum, molybdenum, titanium, iron, zirconium, magnesium, and alloys thereof). Particularly suitable conductive metals include, for example, copper, copper alloys (e.g., copper-zirconium, copper-magnesium, copper-zinc, or copper-iron), nickel, and nickel alloys (e.g., nickel-iron). The thickness of the terminations is generally selected to minimize the thickness of the capacitor. For example, the thickness of the terminations may range from about 0.05 to about 1 millimeter, in some embodiments, from about 0.05 to about 0.5 millimeters, and from about 0.07 to about 0.2 millimeters. One exemplary conductive material is a metal plate of copper-iron alloy available from Wieland (Germany). If desired, the surfaces of the terminations can be electroplated with nickel, silver, gold, tin, etc., as known in the art, to ensure that the final component can be mounted to a circuit board. In one particular embodiment, both surfaces of the terminations are plated with nickel and silver flash, respectively, while the mounting surface is also plated with a tin solder layer.
[0043] The terminations can be connected to the capacitor elements using any technique known in the art. For example, in one embodiment, a lead frame can be provided that defines a cathode termination and an anode termination. To attach the electrolytic capacitor elements to the lead frame, a conductive adhesive can first be applied to the surface of the cathode termination. The conductive adhesive can include, for example, conductive metal particles contained in a resin composition. The metal particles can be silver, copper, gold, platinum, nickel, zinc, bismuth, etc. The resin composition can include a thermosetting resin (e.g., an epoxy resin), a hardener (e.g., an acid anhydride), and a compound (e.g., a silane compound). Suitable conductive adhesives are described in U.S. Patent Application Publication No. 2006 / 0038304 to Osako et al. The conductive adhesive can be applied to the cathode termination using any of a variety of techniques. For example, printing techniques can be used for their practical and cost-saving benefits. The anode lead can also be electrically connected to the anode termination using any technique known in the art, such as mechanical welding, laser welding, conductive adhesives, etc. Once the anode lead has been electrically connected to the anode termination, the conductive adhesive may then be cured to ensure proper adhesion of the electrolytic capacitor element to the cathode termination.
[0044] For example, referring again to FIG. 1, electrolytic capacitor 30 is shown as including an anode termination 62 and a cathode termination 72 in electrical communication with capacitor element 33. Although electrolytic capacitor 30 can be in electrical contact with any of the surfaces of capacitor element 33, cathode termination 72 in the illustrated embodiment is in electrical contact with bottom surface 39 via conductive adhesive 90. More specifically, cathode termination 72 includes a first part 73 in electrical contact with and generally parallel to bottom surface 39 of capacitor element 33. Anode termination 62 similarly includes a first part 63 disposed substantially perpendicular to second part 64. First part 63 is in electrical contact with and generally parallel to bottom surface 39 of capacitor element 33. Second part 64 includes region 51 that holds anode lead 16. Although not shown in FIG. 1, region 51 can have a "U-shape" to further increase surface contact and mechanical stability of lead 16.
[0045] The terminations may be connected to the capacitor elements using any technique known in the art. For example, in one embodiment, a lead frame may be provided that defines the cathode termination 72 and the anode termination 62. To attach the electrolytic capacitor element 33 to the lead frame, a conductive adhesive 90 may first be applied to the surface of the cathode termination 72. The conductive adhesive 90 may include, for example, conductive metal particles contained in a resin composition. The metal particles may be silver, copper, gold, platinum, nickel, zinc, bismuth, and the like. The resin composition may include a thermosetting resin (e.g., an epoxy resin), a hardener (e.g., an acid anhydride), and a coupling agent (e.g., a silane coupling agent). Suitable conductive adhesives are described in U.S. Patent Publication No. 2006 / 0038304 to Osako et al. The conductive adhesive may be applied to the cathode termination 72 using any of a variety of techniques. For example, printing techniques may be used for their practical and cost-saving benefits.
[0046] Various methods may generally be used to attach the terminations to the capacitor. In one embodiment, for example, the second piece 64 of the anode termination 62 is first bent upward to the position shown in FIG. 1. The capacitor element 33 is then placed over the cathode termination 72 such that the bottom surface 39 is in contact with the adhesive 90 and the anode lead 16 is received in area 51. If desired, an insulating material (not shown), such as a plastic pad or tape, may be placed between the bottom surface 39 of the capacitor element 33 and the first piece 63 of the anode termination 62 to electrically isolate the anode and cathode terminations.
[0047] Anode lead 16 is then electrically connected to region 51 using any technique known in the art such as mechanical welding, laser welding, conductive adhesives, etc. For example, a laser can be used to weld anode lead 16 to anode termination 62. Lasers generally include a resonator that contains a laser medium capable of emitting photons by stimulated emission and an energy source that excites the elements of the laser medium. One type of suitable laser is one in which the laser medium is made of aluminum and yttrium garnet (YAG) doped with neodymium (Nd). The excited particles are neodymium ions Nd 3+ The energy source can provide continuous energy to the laser medium to emit a continuous laser beam or an energy discharge to emit a pulsed laser beam. Once the anode lead 16 is electrically connected to the anode termination 62, the conductive adhesive can then be cured. For example, a heat press can be used to apply heat and pressure to ensure that the adhesive properly bonds the electrolytic capacitor element 33 to the cathode termination 72.
[0048] III. Casing The capacitor element is typically enclosed in a casing such that at least a portion of the anode and cathode terminations are exposed for mounting on a circuit board. As shown in FIG. 1, for example, the capacitor element 33 is enclosed in a casing 92 such that a portion of the anode termination 62 and a portion of the cathode termination 72 are exposed. The casing is typically formed from a thermosetting resin. Examples of such resins include, for example, epoxy resins, polyimide resins, melamine resins, urea-formaldehyde resins, polyurethane resins, phenolic resins, polyester resins, and the like. Epoxy resins are particularly suitable. Still other additives may be used, such as photoinitiators, viscosity modifiers, suspension aids, pigments, stress reducers, non-conductive fillers, stabilizers, and the like. For example, non-conductive fillers may include inorganic oxide particles such as silica, alumina, zirconia, magnesium oxide, iron oxide, copper oxide, zeolites, silicates, clays (e.g., smectite clays), and the like, as well as composites (e.g., alumina-coated silica particles), and mixtures thereof. EXAMPLES
[0049] The invention may be better understood with reference to the following examples.
[0050] Test procedure Breakdown Voltage The breakdown voltage was measured at a temperature of 23°C + 2°C using a Keithley 2400 SourceMeter. Each capacitor was assigned the formula: Current (A) = Nominal Capacitance (F) x dU / dt where dU / dt represents the voltage gradient, typically set at 10 V / s. The voltage is measured during charging and the maximum voltage value reached when the applied voltage drops by more than 10% is recorded as the breakdown voltage.
[0051] Equivalent Series Resistance (ESR) The equivalent series resistance can be measured using an HP4284A LCR meter with Kelvin leads, with a DC bias of 0 volts and a 10 mVAC signal. The operating frequency was 100 kHz and the temperature was 23°C + 2°C.
[0052] Loss factor The loss factor can be measured using an LCZHP4284A LCR meter with Kelvin leads, with 0 volts DC bias and a 10 mVAC signal. The operating frequency can be 120 Hz and the temperature can be 23°C ± 2°C.
[0053] capacitance Capacitance was measured using a Keithley 3330 precision LCZ meter with Kelvin leads using a DC bias of 2.2 volts and a sine wave signal of 0.5 volts peak-to-peak. The operating frequency was 120 Hz and the temperature was 23°C ± 2°C.
[0054] Leakage Current The leakage current can be measured using a leakage tester (YHP4140B) at rated voltage and at a temperature of 23°C ± 2°C with a 1 kilohm resistor to limit the charging current after a minimum of 60 seconds (e.g., 60 seconds or 300 seconds).
[0055] Life Test The life test can be performed for 500 hours at a temperature of 85°C and 1.0 times the rated voltage. The test group size is typically 12 samples. During and after the life test, the aged samples are allowed to recover at room temperature for about 60 minutes. The "recovered" DCL can then be measured at rated voltage at a temperature of 23°C + 2°C for about 60 seconds. The duration of the intermediate "recovered" DCL measurements is typically 120 hours.
[0056] Example 1 Anode samples were prepared using 100,000 μFV / g tantalum powder. Each anode sample was packed at 6.0 g / cm 3The pellets were pressed to a density of 10000g / g and sintered at 1275°C. Sintering was followed by a deoxidation process at 860°C, welding of leads, and a second sintering process conducted at 1275°C. The resulting pellets had dimensions of 1.19 x 1.68 x 0.95 mm. The pellets were anodized to 36.8 volts in a water / nitric acid electrolyte having a conductivity of 7.3 mS at a temperature of 85°C to form a dielectric layer. The anode was then oxidized with an aqueous solution of manganese(II) nitrate (1190 kg / m 3 ) for 180 seconds and then decomposed at 250 °C. This step was repeated nine times. The anode was then immersed in an aqueous solution of manganese(II) nitrate (1300 kg / m 3 ) and then decomposed at 250 °C to obtain MnO2 cathode. Finally, the anode was then immersed in graphite dispersion and silver dispersion in sequence and dried. The completed capacitor element was finished by conventional assembly techniques. A large number (500) of 22 μF / 16 V capacitors were thus fabricated.
[0057] Example 2 Capacitors were formed as described in Example 1, except that the first sintering step was skipped and the deoxidation process temperature was 960° C. A number of parts (500) of 22 μF / 16 V capacitors were made in this manner.
[0058] Example 3 Capacitors were formed as described in Example 2, except that 150,000 μFV / g tantalum powder was used. The pellets were anodized to 40 volts. A number of parts (500) of 22 μF / 16V capacitors were made in this manner.
[0059] Example 4 Capacitors were formed as described in Example 2, except that 200,000 μFV / g tantalum powder was used and the anodes were sintered at 1225° C. The pellets were anodized to 40 volts. A number of parts (500) of 22 μF / 16V capacitors were made in this manner.
[0060] The average leakage current characteristics of the completed capacitors and after life testing were measured, and the results are shown below.
[0061] [Table 1]
[0062] [Table 2] These and other modifications and variations of the present invention may be implemented by those skilled in the art without departing from the spirit and scope of the present invention. Moreover, it should be understood that aspects of the various embodiments may be interchanged both in whole or in part. Moreover, those skilled in the art will recognize that the above description is by way of example only and is not intended to limit the invention as further described in the appended claims.
Claims
1. 1. A solid electrolytic capacitor comprising a capacitor element, the capacitor element comprising a deoxidized and sintered anode body formed from tantalum powder having a specific charge of about 100,000 to about 350,000 μF·V / g, a dielectric comprising tantalum pentoxide disposed on the anode body, and a solid electrolyte disposed on the dielectric, the capacitor having a dielectric strength of about 0.4 V / nm or greater, an aged DCL of about 0.5 μA or less, and a dielectric constant of about 0.01 to about 0.05 μA, the dielectric constant being determined by the formula: Normalized Aged Leakage Current=100×(Aged DCL / CV) (In the formula, Aged DCL is the leakage current measured at about 23° C. and rated voltage for about 60 seconds after the capacitor has been subjected to a life test at 85° C. and rated voltage for 120 hours and then allowed to recover at about 23° C. for 60 minutes; C is the initial capacitance (in Farads) desired at a temperature of approximately 23° C. and an operating frequency of 120 Hz; V is the rated voltage (volts) The solid electrolytic capacitor exhibits a normalized aged leakage current of about 0.075% or less, as determined according to
2. 2. The solid electrolytic capacitor of claim 1, wherein the aged DCL is about 0.25 μA or less.
3. 10. The solid electrolytic capacitor of claim 1, wherein the solid electrolyte comprises manganese dioxide.
4. an anode termination in electrical communication with the anode body; a cathode termination in electrical communication with the solid electrolyte; and a housing that encases the capacitor element and leaves at least a portion of the anode termination and the cathode termination exposed; The solid electrolytic capacitor of claim 1 further comprising:
5. The solid electrolytic capacitor of claim 4 , wherein the housing is formed from a resinous material that encapsulates the capacitor element.
6. 2. The solid electrolytic capacitor of claim 1, wherein the powder has a specific charge of about 100,000 to about 300,000 μF·V / g.
7. 1. A method of forming a solid electrolytic capacitor, comprising: forming an anode by a process including compressing a powder comprising tantalum having a specific charge of about 100,000 to about 350,000 μF·V / g into a porous anode body, subjecting the porous anode body to a deoxidization process to form a deoxidized anode body, and sintering the deoxidized anode body; anodizing the deoxidized and sintered anode body at a forming voltage of about 35 volts or greater to form a dielectric comprising tantalum pentoxide disposed over the anode body; forming a solid electrolyte disposed over the dielectric; Including, The capacitor has a dielectric strength of about 0.4 V / nm or greater, an aged DCL of about 0.5 μA or less, and a dielectric constant of about 0.2 μA or less, the following formula: Normalized Aged Leakage Current=100×(Aged DCL / CV) (In the formula, Aged DCL is the leakage current measured at about 23° C. and rated voltage for about 60 seconds after the capacitor has been subjected to a life test at 85° C. and rated voltage for 120 hours and then allowed to recover at about 23° C. for 60 minutes; C is the initial capacitance (in Farads) desired at a temperature of approximately 23° C. and an operating frequency of 120 Hz; V is the rated voltage (volts) The method of claim 1, wherein the normalized aged leakage current is less than or equal to about 0.075%, as determined according to
8. The method of claim 7 , wherein an anode lead is connected to the porous anode body.
9. The method of claim 7 , wherein the deoxidation process comprises inserting the porous anode body into a housing containing a getter material.
10. The method of claim 9, further comprising heating the atmosphere of the enclosure to a temperature of about 700° C. to about 1,200° C.
11. The method of claim 7, wherein the sintering step occurs at a temperature of about 700°C to about 1,600°C.
12. The method of claim 7 further comprising the step of pre-sintering the porous anode body prior to the deoxidation process.
13. 8. The method of claim 7, wherein the aged DCL is about 0.25 μA or less.
14. The method of claim 7, wherein the powder has a specific charge of about 100,000 to about 300,000 μF·V / g.
15. The method of claim 7 , wherein the solid electrolyte comprises manganese dioxide.
16. 10. The solid electrolytic capacitor of claim 1, wherein a moisture barrier layer is disposed over the solid electrolyte.
17. The solid electrolytic capacitor of claim 1 , wherein there is no pre-sintering step prior to said deoxidization.
18. The method of claim 7 further comprising forming a moisture barrier layer disposed over the solid electrolyte.
19. The method of claim 7 , which does not include a pre-sintering step prior to said deoxidization.
20. The deoxidized and sintered anode body has a mass of about 1 kilogram (kg f The solid electrolytic capacitor according to claim 1 , which exhibits a compressive strength of at least 100%.
Citation Information
Patent Citations
Anode for solid electrolytic capacitor containing non-metallic surface treatment
JP2010199572A
Solid electrolytic improved in performance under high voltage
JP2014022749A
Tantalum Powder, Anode, And Capacitor Including Same, And Manufacturing Methods Thereof
US20180144874A1
Sintered tantalum and niobium capacitor pellets doped with nitrogen, and method of making the same
WO2002045109A1
Method for manufacturing metal powder, method for manufacturing porous sintered body, metal powder, and capacitor
WO2006062234A1